2013
DOI: 10.1089/jamp.2011.0932
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution During Pregnancy and Neonatal Outcome: A Review

Abstract: There is increasing evidence of the adverse impact of prenatal exposure to air pollution. This is of particular interest, as exposure during pregnancy--a crucial time span of important biological development--may have long-term implications. The aims of this review are to show current epidemiological evidence of known effects of prenatal exposure to air pollution and present possible mechanisms behind this process. Harmful effects of exposure to air pollution during pregnancy have been shown for different birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
68
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 123 publications
2
68
0
5
Order By: Relevance
“…Exposure to PM 2.5 has also been linked to low lung function in 4-year-old children in a birth cohort study in the Netherlands (Eenhuizen et al, 2012), supporting previously published studies that reported effects of PM 2.5 on lung function development, reviewed in Götschi et al (2008). Evidence is increasing for an association of ambient air pollution, including fine particles, with birth outcomes (Parker et al, 2011;Proietti et al, 2013;Ritz & Wilhelm, 2008). A systematic review reported significant associations between exposure to PM 2.5 and birth outcomes, including low birth weight, preterm birth and small for gestational age births (Shah & Balkhair, 2011).…”
supporting
confidence: 73%
“…Exposure to PM 2.5 has also been linked to low lung function in 4-year-old children in a birth cohort study in the Netherlands (Eenhuizen et al, 2012), supporting previously published studies that reported effects of PM 2.5 on lung function development, reviewed in Götschi et al (2008). Evidence is increasing for an association of ambient air pollution, including fine particles, with birth outcomes (Parker et al, 2011;Proietti et al, 2013;Ritz & Wilhelm, 2008). A systematic review reported significant associations between exposure to PM 2.5 and birth outcomes, including low birth weight, preterm birth and small for gestational age births (Shah & Balkhair, 2011).…”
supporting
confidence: 73%
“…A steadily growing body of literature has implicated maternal exposure to air pollution as a potential causal factor in offspring adverse birth outcomes, including infant mortality, low birth-weight, and preterm birth (Proietti et al, 2013; Shah et al, 2011; Stieb et al, 2012). Emerging data also suggests a link between air pollution and congenital anomalies (E.K.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evidence indicates that prenatal exposure to outdoor air pollution is associated with risk of term low birth weight (Brauer et al, 2008;Fleischer et al, 2014;Ghosh et al, 2013Ghosh et al, , 2012Hyder et al, 2014;Padula et al, 2012;Parker et al, 2011;Ponce, 2005;Proietti et al, 2013;Ritz and Wilhelm, 2008;Shah and Balkhair, 2011;Stieb et al, 2012;Wilhelm et al, 2011;Wu et al, 2011). While TLBW contributes to racial-ethnic and socioeconomic health disparities in the United States, air pollution is thought to be an important place-based factor in the complex geography of and susceptibly to TLBW MorelloFrosch and Shenassa, 2006).…”
Section: Introductionmentioning
confidence: 99%